Maternal Mortality in the United States. Issue 5 (September 2019) - Simpson, Kathleen Rice
Abstract : Maternal mortality rates in the United States compare very unfavorably with other high-income countries. The Centers for Disease Control and Prevention estimate that about 700 women die of pregnancy-related causes in the United States each year. A summary of their May 2019 report is presented. Nurses must continue to take a leadership role in efforts to reduce the unacceptably high maternal mortality in the United States.